Syntheses, structures and anticancer activities of CuII and ZnII complexes containing 1,1′-[(3-fluorophenyl)methylene]bis[3-(3-fluorophenyl)imidazo[1,5-a]pyridine] - Hai Le Thi Hong; Hau Nguyen Van; Duong Hoang Tuan; Hung Tran Quang; Tuan Dang Thanh; Luc Van Meervelt (Acta Crystallographica Section E: Crystallographic Communications)
Two novel complexes, [Cu(T4)Cl2] and [Zn(T4)Cl2], were synthesized from 1,1′-[(3-fluorophenyl)methylene]bis[3-(3-fluorophenyl)imidazo[1,5-a]pyridine] (T4), and copper(II) and zinc(II) chloride, respectively. The structures of these complexes were confirmed using ESI-MS, IR and 1H NMR spectra. The results reveal mononuclear structures in which the central metal atoms are coordinated by two N atoms from the imidazole rings and two Cl ligands. The structure of the CuT4 complex [systematic name: dichlorido{1,1′-[(3-fluorophenyl)methylene]bis[3-(3-fluorophenyl)imidazo[1,5-a]pyridine]-κ2N,N′}copper(II), [CuCl2(C33H21F3N4)], was confirmed by single-crystal X-ray diffraction. The CuII atom adopts a distorted tetrahedral coordination environment with an N2Cl2 coordination set. The predominant features of the crystal packing are C—H...F, C—H...π and C—F...π interactions. Biological evaluations demonstrated that both complexes exhibit enhanced anticancer activity compared to the free ligand, with IC50 values ranging between 18.93 and 67.06 µM. Notably, the CuII complex displays excellent inhibitory activity against the MCF7 breast cancer cell line (IC50 = 27.99 µM), approximately twice as effective as cisplatin. Conversely, the ZnT4 complex shows greater efficacy against Hep-G2 and A549 lung cancer cell lines, with IC50 values between 18.93 and 24.83 µM. The results suggest that CuII and ZnII complexes of T4 show potential as cancer treatment agents.